Evaluation of the spread of SARS CoV-2 at the start of the COVID-19 epidemic in four sub-Saharan African countries - (:unkn) unknown (My University, 2025)
General aim of the project and the issues involvedAt the end of October 2020, the data available for the African continent showed 1.6 million reported cases and almost 40,000 deaths, giving a case-fatality rate of 2.5%. The Afracov2 project aims to assess the spread of SARS-CoV-2 in sub-Saharan Africa, through a serological study of blood donors in four countries from the Groupe de recherches transfusionnelles d'Afrique Francophone (Burkina Faso, Cameroon, Madagascar and Mali). Around 1,200 samples per country were set aside during the initial phases of the COVID-19 epidemic, from March 2020 to March 2021. The detection of potential antibodies produced during infection by this virus was carried out retrospectively, in order to study its prevalence in the blood donor population, which mirrors the general population. ResultsPrevalence, i.e. the number of samples found to be positive per unit of time, was found to be high relatively early in the time study, already reaching 20% of blood donors in May 2020. In January 2021, it represented between 25% and 30% of samples, for antibodies indicating a recent infection. By comparison, in May 2020 in France, it was estimated at 3.3%, a much lower figure, perhaps due to the health measures introduced in March 2020 (notably containment). These results suggest that the spread of COVID-19 may have been more rapid in sub-Saharan Africa than in Europe.
Keywords: African Research